Zbirka nalog iz geodezije - Kamnik, Rok (University of Maribor Press, 2025)
Collection of Geodesy Tasks. The collection of tasks in geodesy includes tasks for exercises in the subjects of Geodesy, Selected chapters in geodesy and GIS, Geodesy/GIS - selected chapters. As an aid in learning about basic solutions to geodetic problems for the needs of civil engineers, it can also be used by students of other faculties and study programs who encounter Geodesy. The collection of tasks is divided into the following sections: Introduction, units of length and angle, calculating angles, specifying accuracy, plans, cartography, topography, calculating point coordinates, calculating staked elements, calculating elevation points, calculating areas and volumes, project tasks, GIS tasks, other tasks with a computer and field tasks.